ANALISIS PENDAPATAN PETANI NANAS BERDASARKAN POLA USAHA DI DESA TANGKIT BARU KECAMATAN SUNGAI GELAM KABUPATEN MUARO JAMBI - Damai Gaja, Dian; Damayanti, Yusma; Kernalis, Emy (Universitas Jambi, 2019)
This research purposed (i) to know how much cost, revenue, and income that farmer get from pineapple farming (ii) to know farmer’s income from another farming and from outside farming sector (iii) to know how much contribution income from pineapple farming based on the pattern of efforts in research area. This research started in Tangkit Baru Village Sungai Gelam District Muaro Jambi Regency choosen by purposive. The data usedare primary and secondary data. The method analysis of data used is income analysis and contribution analysis. To determine respondent that used simple random sampling by choose the farmer with judgement that farmer is homogeny look from pineapple farming or outside pineapple farming. Total respondent in this research are 40 farmers. The biggest average income from farming pineapple in Tangkit Baru Village is Rp. 48.028.833/ year. This is based on the pattern of farming pineapple and patin fish. The biggest average income from another farming, that is in the pattern of farming pineapple and farming gurami fish, that get Rp. 28.962.714/year. The biggest average income from effort in the outside of farming sector is outlet airplane ticket, that is Rp. 34.250.000/year. Contribution income of farming pineapple toward farmer’s income according the biggest of pattern effort is farming pineapple an patin fish that is 73,60%.